2019
DOI: 10.1002/pmrj.12066
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Falls in Adults with Knee Osteoarthritis: A Systematic Review

Abstract: Objective To examine the evidence of risk factors for falls in adults with knee osteoarthritis (OA). Type Systematic Review. Methodology A systematic literature search was performed in 9 electronic databases from inception to July 2016. Two reviewers screened articles using set inclusion and exclusion criteria. Observational study designs that included participants with knee OA and history of falls were considered. Results reported as odds ratios, relative risks, prevalence ratios, or hazard ratios were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 56 publications
0
81
0
4
Order By: Relevance
“…The prevalence of RA in South Korea estimates was 0.27% in 2008 [24]. Interestingly, contrary to previous results regarding the relevance of falls and arthritis, there have been different opinions from some experts [25,26]. Some OA studies reported no association between knee pain and a fall, and they even suggested that pain was protective against falls [27][28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of RA in South Korea estimates was 0.27% in 2008 [24]. Interestingly, contrary to previous results regarding the relevance of falls and arthritis, there have been different opinions from some experts [25,26]. Some OA studies reported no association between knee pain and a fall, and they even suggested that pain was protective against falls [27][28][29][30].…”
Section: Discussionmentioning
confidence: 91%
“…Few studies have obtained data on fall occurrence prospectively in relationship to knee pain ( 18 ). A study by Dore et al suggested that the presence of lower limb OA in one site led to a 53% increase the risk of future falls in 12 months ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…During stair climbing or descent, people with KOA both have altered kinematics changes in sagittal plane and delayed quadriceps muscle activity 4 5. Impaired postural control and balance, reduced knee muscle strength, poor proprioceptive acuity and joint symptoms have been postulated to elevate fall risks in this population 6 7. Therapeutic strategies addressing these potential underlying neuromechanical factors have been advocated to prevent falls 7 8…”
Section: Introductionmentioning
confidence: 99%
“…Impaired postural control and balance, reduced knee muscle strength, poor proprioceptive acuity and joint symptoms have been postulated to elevate fall risks in this population 6 7. Therapeutic strategies addressing these potential underlying neuromechanical factors have been advocated to prevent falls 7 8…”
Section: Introductionmentioning
confidence: 99%